2014
DOI: 10.7717/peerj.348
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the relationship between invasive lionfish and native grouper in the Caribbean

Abstract: Biotic resistance is the idea that native species negatively affect the invasion success of introduced species, but whether this can occur at large spatial scales is poorly understood. Here we re-evaluated the hypothesis that native large-bodied grouper and other predators are controlling the abundance of exotic lionfish (Pterois volitans/miles) on Caribbean coral reefs. We assessed the relationship between the biomass of lionfish and native predators at 71 reefs in three biogeographic regions while taking int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 62 publications
7
45
0
4
Order By: Relevance
“…Mesocosm experiments have shown little effect of native grouper presence on lionfish behaviors (Morris 2009, Raymond et al 2015. Furthermore, it has been widely debated whether mesopredators such as groupers actually function as biocontrol for invasive lionfish (see Mumby et al 2011 and subsequent responses by Hackerott et al 2013 andValdivia et al 2014). However, Pusack (2013) reported that Nassau grouper appeared to reduce the effect of lionfish predation on native reef fish abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Mesocosm experiments have shown little effect of native grouper presence on lionfish behaviors (Morris 2009, Raymond et al 2015. Furthermore, it has been widely debated whether mesopredators such as groupers actually function as biocontrol for invasive lionfish (see Mumby et al 2011 and subsequent responses by Hackerott et al 2013 andValdivia et al 2014). However, Pusack (2013) reported that Nassau grouper appeared to reduce the effect of lionfish predation on native reef fish abundance.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there is wide variation in lionfish densities within their invaded range, owing in part to differences in the length of time since establishment (Ruttenberg et al 2012, Dahl & Patterson 2014, removal efforts (Frazer et al 2012, de León et al 2013, and abiotic site characteristics including depth and exposure to strong currents and wave surge (Whitfield et al 2007, Anton et al 2014. In contrast, invasive lionfish populations are likely unaffected by potential predators (Hackerott et al 2013, Valdivia et al 2014, but see Mumby et al 2011) or interspecific competitors (Albins 2013), especially given that native predators are severely depleted throughout much of the Caribbean (Paddack et al 2009, Stallings 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Native predators are apparently de - terred by the unusual shape, cryptic coloration, and venomous spines of lionfish, although there is debate regarding whether large native groupers are a major threat to the invader (Mumby et al 2011, Hackerott et al 2013, Valdivia et al 2014. Few parasites attack invasive lionfish (Sikkel et al 2014), native mesopredators appear to be ineffective competitors (Albins 2013), and even highly territorial damselfish do not chase them (Kindinger 2015).…”
mentioning
confidence: 99%